The Influence of Rock Properties and Size into Strength Criteria: A Proposed Criterion for Soft Rock Masses - Agustawijaya D.S. (Civil Engineering Dimension, 2011)
A new modified strength criterion for soft rock masses is proposed in this paper in order to provide a suitable estimation for soft rock mass strength. The new criterion is based upon the current compression test data of soft materials of over 150 samples, and available published data of soft rock strength. It is shown that the proposed criterion estimates reasonable values of soft rock mass strength. Rock properties and size contribute significantly into the strength, represented by friction angle and unconfined compressive strength. Examples exercised reveal that the structure of soft rock masses takes a dominant part in controlling the strength, which then determines the modelled strength of soft rock masses. The results also show that the strength of the proposed equation could relatively be higher three times than the strength of the Hoek-Brown criterion for a massive soft rock mass.